2014
DOI: 10.20453/rnp.v76i2.1194
|View full text |Cite
|
Sign up to set email alerts
|

Despersonalización: más que síntoma, un síndrome.

Abstract: RESUMENLa despersonalización es un fenómeno psicopatológico consuetudinariamente soslayado, considerado un simple elemento sintomático unidimensional formando parte de otros síndromes de mayor complejidad. En los últimos años la investigación psicopatológica y neurobiológica ha permitido identificar diversos componentes de la despersonalización que permitirían caracterizarla más propiamente como un síndrome con correlatos funcionales de desconexión córtico-subcortical. Sobre la base de cuatro casos de desperso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
1
0
0
2
Order By: Relevance
“…In the three dimensions that make up the Maslach Burnout Inventory, in our research, we found significant gender differences in depersonalization and self-fulfillment. The results indicate that males obtained higher levels of depersonalization, an alteration of the consciousness of the self, in such a way that the depersonalized individual feels himself as strange and distant, a mere observer of his mental processes and his bodily sphere [85]. These results are supported by other research, which also shows higher levels in males than in females [86,87].…”
Section: Discussionsupporting
confidence: 79%
“…In the three dimensions that make up the Maslach Burnout Inventory, in our research, we found significant gender differences in depersonalization and self-fulfillment. The results indicate that males obtained higher levels of depersonalization, an alteration of the consciousness of the self, in such a way that the depersonalized individual feels himself as strange and distant, a mere observer of his mental processes and his bodily sphere [85]. These results are supported by other research, which also shows higher levels in males than in females [86,87].…”
Section: Discussionsupporting
confidence: 79%
“…Se asocia con irritabilidad, insensibilidad, indiferencia, culpa y falta de motivación para el trabajo. La despersonalización es común en los campos psiquiátrico y neurológico; sin embargo, una gran proporción de personas normales pueden experimentar situaciones ordinarias de agotamiento físico o emocional, estrés o falta de sueño (Cruzado et al, 2013).…”
Section: Pág 4677unclassified
“…− Despersonalización: Es una perturbación de la parte del yo de la persona, manifestando extrañeza y distancia de sí mismo (50).…”
Section: Marco Conceptualunclassified